OCEANS 2016 - Shanghai 2016
DOI: 10.1109/oceansap.2016.7485517
|View full text |Cite
|
Sign up to set email alerts
|

On received intensity for misaligned underwater wireless optical links

Abstract: In underwater wireless optical communications (UWOC), alignment is a key factor to establish a precisely aligned link between the source and detector. In this paper, we consider the condition of link misalignment and extend the stochastic channel model verified by Monte Carlo simulations taking absorption and scattering into account in turbid water. And we investigate the received intensity in the presence of link misalignment caused by the detector elevation angle, azimuth angle and field-of-view (FOV). Numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The performance of an UWOC system considering the link alignment for a collimated laser source was investigated in [17] by driving a closed‐form expression to outline the relationship between the transmit power, link span and the receiver (Rx) offset distance. In [18] the effect of elevation angle and field of view (FOV) of a Rx on the link misalignment for a collimated transmitted beam was reported. In [19] it was shown that the received light intensity decreases when both the divergence and elevation angles of a diffused point source increase.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of an UWOC system considering the link alignment for a collimated laser source was investigated in [17] by driving a closed‐form expression to outline the relationship between the transmit power, link span and the receiver (Rx) offset distance. In [18] the effect of elevation angle and field of view (FOV) of a Rx on the link misalignment for a collimated transmitted beam was reported. In [19] it was shown that the received light intensity decreases when both the divergence and elevation angles of a diffused point source increase.…”
Section: Introductionmentioning
confidence: 99%
“…The angle-of-elevation (AOE) and FOV of the Rx usually gets affected by the link misalignment. Also, when the AOE and the divergence angle for a point source are disturbed, it leads to a reduction in the received power [33]. In the literature, many solutions have been proposed to tackle the misalignment between the Tx and the Rx for performance improvement.…”
Section: Literature On O-ioutmentioning
confidence: 99%
“…The above-mentioned process is repeated to record the motion pro- cess of the photon. 19 In the process of motion, photons collide with particles to produce scattering and absorption, and the weight of photons decreases after collision. The weight of the photons before and after collision is Wpost = Wpre ⋅ W th , where W th = b/c is the scattered albedo, which is the ratio of scattering to total attenuation.…”
Section: Introductionmentioning
confidence: 99%